The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/foods10081685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Processing Methods and Internal Components on Physicochemical Properties and Glycemic Index of Adzuki Bean Powder

Abstract: The estimated glycemic index (eGI) value of adzuki bean powder prepared by steamed cooking (SC), extruded cooking (EC) and roller cooking (RC) was studied comparatively. Results showed that RC had the highest eGI, with 80.1, and both EC and SC resulted in a lower eGI value of 70.0 and 49.7, respectively. Compared with the EC and RC methods, the SC method provided a more intact physical barrier for starch digestion, resulting in a less destroyed cell structure. As the essential components that form the cell wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…1 < G24. The GIs of these adzuki beans were lower than those of whole beans (81), mung beans (82), and adzuki beans (83). Previous studies have suggested that phenolics impose positive effects on postprandial blood glucose levels in aspects of inhibiting amylase activities, decreasing glucose absorption, 10.3389/fnut.2022.1063602 and stimulating insulin secretion.…”
Section: Discussionmentioning
confidence: 81%
“…1 < G24. The GIs of these adzuki beans were lower than those of whole beans (81), mung beans (82), and adzuki beans (83). Previous studies have suggested that phenolics impose positive effects on postprandial blood glucose levels in aspects of inhibiting amylase activities, decreasing glucose absorption, 10.3389/fnut.2022.1063602 and stimulating insulin secretion.…”
Section: Discussionmentioning
confidence: 81%
“…Food integrity and structure also influence GR in people with T2D ( 14 , 44 , 53 55 ). Those foods that preserve their original structure, without being subjected to any processing technique ( 27 , 56 ), expose their nutrients within the food matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown the importance of maintaining food structure in order to reduce GR ( 53 55 ). Comparing the size particles of foods such as oats (flour vs. flakes), an increase in blood glucose was observed after consuming the flour due to a greater availability of starch compared to whole flakes.…”
Section: Resultsmentioning
confidence: 99%